Nursing students’ views about graphic warnings and texts on cigarettes and their nicotine dependence - Ceylan, Erdal; Uysal, Neşe; Koç, Ayşegül (Journal of Dependence, 2020)
Objective: This study was conducted to determine smoker nursing students’ thoughts about graphic warnings and texts on cigarette packs, impact of these warnings on their cigarette consumption and their nicotine dependence levels.Method: The sample of the study consisted of 82 smoker nursing students and 89.1% of aimed population has been reached. Data was collected by both the questionnaire developed by the researchers and Fagerström Test for Nicotine Dependence (FTND).Results: Most graphic warnings on the packs were ineffective and the one found to be effective pictures are those containing the horror element. The rate of those who think about quitting smoking after seeing the pictures is 19.5%. A positive correlation was found between the number of cigarettes consumed per day, the number of illnesses due to smoking and the mean FTND score.Conclusion: Graphic warnings on cigarette packs were generally found to be ineffective in reducing smoking. Printing dramatic, frightening and indicating more serious health problems images that span more space on cigarette packs can be effective in reducing the use of tobacco products.
Keywords: Students; nursing; tobacco use disorder; tobacco products